1990
DOI: 10.1002/polb.1990.090280405
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of cationic polyelectrolytes in aqueous solution

Abstract: Four different fluoride, chloride, bromide, and nitrate cationic polyelectrolytes were prepared. Their electrolytic conductivity in aqueous dilute solution was investigated. The results show a remarkable increase, with dilution being practically constant down to limiting concentration. The limiting equivalent conductivity Λ° follows the order $\[ {\rm F}^ - \gg {\rm Cl}^ - > {\rm Br}^ - \approx {\rm NO}_3^ - \]$ The distances between neighboring charges calculated from experimental data are in good agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…However, the main application of this type of molecule is found in the mining industry because of the enormous amounts of product required to float minerals. Interactions of aliphatic xanthates and cationic micelles have been studied (5), and a method for exchanging counterions has been proposed and successfully used in cationic micelles (6) and polyelectrolytes (7). Complexes of xanthates have been recently used as antiviral and antitumoral compounds (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, the main application of this type of molecule is found in the mining industry because of the enormous amounts of product required to float minerals. Interactions of aliphatic xanthates and cationic micelles have been studied (5), and a method for exchanging counterions has been proposed and successfully used in cationic micelles (6) and polyelectrolytes (7). Complexes of xanthates have been recently used as antiviral and antitumoral compounds (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Conductivity measurements for many polyelectrolyte systems have been reported, but only a few studies on concentration effects over an extended concentration range can be found 17–29. Moreover, most of these studies have been carried out on anionic polyelectrolytes 18, 21, 24–33. In most cases, the results show that the molar conductivity increases with decreasing concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylic and sulfonic acid groups are among the most interesting and studied functional groups. The interactions between series of PEs such as poly(carboxylic acid)s, poly(acrylic acid) (PAA), and poly(methacrylic acid), poly(vinyl sulfonic acid) (PVSA), poly(2‐acrylamido‐2‐methyl‐1‐propane sulfonic acid), and several cations have been studied by potentiometric and spectroscopic techniques as well as LPR 27–38. Polymers containing sulfonic acid moieties, such as PVSA, do not act as ligands, but the functional‐group/metal‐ion interaction is predominantly of the electrostatic type.…”
Section: Introductionmentioning
confidence: 99%